Transformasi Ekonomi Syariah di Era Digital: Analisis Konseptual terhadap Integrasi Fintech dan Maqāṣid al-Sharī‘ah - Muchamat Amarodin; Nurwahyuni Nurwahyuni; Mohammad Saiful Rifai (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The development of digital technology has driven major changes in the global financial system, including in the Islamic economic sector through the emergence of financial technology (fintech). This phenomenon presents opportunities for increased efficiency and financial inclusion, but also raises the need for integration that aligns with Islamic principles. This study aims to analyze the characteristics of Islamic economic transformation in the digital era, identify forms of fintech integration within the Islamic economic system, explain the role of maqāṣid al-sharī'ah as an evaluative framework, and formulate a conceptual model of fintech integration based on Islamic values. The study uses a qualitative approach based on library research, with an integrative literature review. Data were obtained from scientific journals, academic books, policy documents, and other relevant publications, then analyzed using content analysis and thematic analysis. The results show that fintech integration in the Islamic economy is developing through peer-to-peer financing services, digital payments, and Islamic crowdfunding that adapt contracts such as mudhārabah, musyārakah, murābaḥah, and wakālah. Other findings indicate that the maqāṣid al-sharī'ah (Islamic principles) play a crucial role in assessing the security, fairness, transparency, and social welfare of digital innovation. This study concludes that the transformation of the Islamic economy will be more sustainable if fintech is developed through a synergy between technology, regulation, governance, and maqāṣid al-sharī'ah orientation, thus creating a modern, inclusive, and valuable digital financial ecosystem.